Anti-crisis Management Strategies: an Empirical Approach = Strategie zarządzania antykryzysowego - ujęcie empiryczne - Starosta, Anna (Zielona Góra: Faculty of Economics and Management Press)
A growing need to function in a crisis makes enterprises take measures related to the prevention and prediction of crises and when they occur to react quickly. Effective crisis coping requires anti-crisis management. However, it is not always possible to prevent crises; moreover, enterprises are forced to make a number of anti-crisis measures.
Keywords: zarządzanie antykryzysowe; działania antykryzysowe; strategie antykryzysowe; anti-crisis management; anti-crisis measures; anti-crisis strategies